Jejunal intussusception in an adult due to small intestine lipomatosis: a case report and review of literature - Raman, Bhavana Venkata Satya; Bandlamudi, Suryanarayana; Rao, Danaboyina Ankkama (International Journal of Research in Medical Sciences, 2017)
Intussusception is rare in adults. Benign neoplasm are common causes for intussusception in adults, lipoma is the commonest. Lipomas are usually solitary but 5% are multiple. Lipomatosis of small bowel is rare condition and presenting, as intestinal obstruction is even rarer. A 55 year old male patient presented with pain abdomen, distention and constipation. CECT revealed intussusception due to multiple lipomas of jejunum causing jejunojejunal intussusception. On exploratory laparotomy bowel was gangrenous and hence a resection and anastomosis was done. On 12 months fallow up patient was normal. First described by Helmstrom in 1906. Fat deposition in intestine are classified as isolated lipoma, multiple lipomas, nodular lipomatosis and diffuse fatty infiltration of wall without projecting into lumen. Usually present as malena or intussusception, volvulus. Radiologically identified by “pseudo kidney sign” and “target sign”. Reduction should not be attempted in the signs of ischemia or malignancy. Lipomatosis should kept in mind as one of the cause for intussusception in adults and CECT is the best modality to ascertain the nature of lesion in most of the cases.